The Venom of One of the World’s Most Deadly Spiders may Provide a Novel Drug to Treat Heart Attack and Stroke Patients and Save Lives - Cock, Ian E (Pharmacognosy Communications)
Approximately 500 years ago, the Swiss philosopher Paracelsus noted that the dose was the important factor in toxicity and that medicines were in fact toxins used at therapeutic doses. Based on that principle, there is a branch of medical research that examines venoms for therapeutic properties to identify potential drug targets. Professor Glenn King from the Institute for Molecular Biosciences at the University of Queensland, Australia leads a group that screens venoms from spiders, scorpions and centipedes, focusing on treatments for pain, epilepsy and stroke. Interestingly, that group recently identified a compound in the venom of a funnel-web spider that is native to K’gari Island, Australia (formerly known as Fraser Island) that blocks cellular mechanisms that induce death of brain and heart cells.1,2 It is believed that by blocking these events, the toxic compound may be useful in decreasing/preventing death associated with heart attack and stroke. The group is currently evaluating the toxicity parameters of the compound, which is necessary to establish to undertake clinical trials through the Therapeutic Goods Administration (TGA) and US Federal Drug Administration (FDA). The group is nearing the end of this process and hopes to begin clinical trials to treat patients suffering from serious heart attack in 2025. Furthermore, it is hoped that the drug will be made available clinically within five years.